Treatment with functionalized designer self‐assembling peptide hydrogels promotes healing of experimental periodontal defects. (6th October 2020) - Matsugami, Daisuke; Murakami, Tasuku; Yoshida, Wataru; Imamura, Kentaro; Bizenjima, Takahiro; Seshima, Fumi; Saito, Atsushi
Abstract: Background/Objectives: It has been reported that self‐assembling peptide (SAP) hydrogels with functionalized motifs enhance proliferation and migration of host cells. How these designer SAP hydrogels perform in the treatment of periodontal defects remains unknown. This study aimed to test the potential of local application of designer SAP hydrogels with two different functionalized motifs in the treatment of experimental periodontal defects. Material and Methods: In vitro, viability/proliferation of rat periodontal ligament‐derived cells (PDLCs) cultured on an SAP hydrogel RADA16 and RADA16 with functionalized motifs, PRG (integrin binding sequence) and PDS (laminin cell adhesion motif), was assessed. Cell morphology was analyzed by scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). In vivo, standardized periodontal defects were made mesially in the maxillary first molars of Wistar rats. Defects received RADA16, PRG, PDS or left unfilled. At 2 or 4 weeks postoperatively, healing was assessed by microcomputed tomography, histological and immunohistochemical methods. Results: Viability/proliferation of PDLCs was significantly greater on PRG than on RADA16 or PDS at 72 hours. rPDLCs in the PRG group showed enhanced elongations and cell protrusions. In vivo, at 4 weeks, bone volume fractions in the PRG and PDS groups were significantly greater than the RADA16 group. Histologically, bone formation was more clearly observed in the PRG and PDS groups compared with the RADA16 group. At 4 weeks, epithelial downgrowth in the hydrogel groups was significantly reduced compared to the Unfilled group. In Azan‐Mallory staining, PDL‐like bundles ran in oblique direction in the hydrogel groups. At 2 weeks, in the area near the root, proliferating cell nuclear antigen (PCNA)‐positive cells were detected significantly more in the PRG group than other groups. At 4 weeks, in the middle part of the defect, a significantly greater level of vascular endothelial growth factor (VEGF)‐positive cells and α‐smooth muscle actin (SMA)‐positive blood vessels were observed in the PRG group than in other groups. Conclusion: The results indicate that local application of the functionalized designer SAP hydrogels, especially PRG, promotes periodontal healing by increasing cell proliferation and angiogenesis.